2021
DOI: 10.1136/bmjopen-2020-044517
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness among older adults in the community during COVID-19: a cross-sectional survey in Canada

Abstract: ObjectivePhysical distancing and stay-at-home measures implemented to slow transmission of novel coronavirus disease (COVID-19) may intensify feelings of loneliness in older adults, especially those living alone. Our aim was to characterise the extent of loneliness during the first wave in a sample of older adults living in the community and assess characteristics associated with loneliness.DesignOnline cross-sectional survey between 6 May and 19 May 2020.SettingOntario, Canada.ParticipantsConvenience sample o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 58 publications
8
81
2
Order By: Relevance
“… 50 Both young and older adults were at risk of loneliness and its consequences for their well-being. 51 , 52 Lower levels of general health, physical function, and spiritual well-being were also associated with older age. 33 , 53 The time since diagnosis had no correlation with the QLI score or its subscales.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Both young and older adults were at risk of loneliness and its consequences for their well-being. 51 , 52 Lower levels of general health, physical function, and spiritual well-being were also associated with older age. 33 , 53 The time since diagnosis had no correlation with the QLI score or its subscales.…”
Section: Discussionmentioning
confidence: 99%
“…The authors in [ 16 ] study the neurobiology of loneliness and listed different sensor-based markers related to loneliness, such as various tomographies or Electroencephalography (EEG). The recent survey in [ 17 ] deals with loneliness of older adults during the COVID-19 era. No quantified metrics are used there; rather, the analysis is based on self-reported data.…”
Section: Progress Beyond the State Of The Artmentioning
confidence: 99%
“…Innovations, such as Wii Bowling, can provide new opportunities for socializing and, as a result, minimize loneliness [ 69 ]. While the COVID-19 pandemic has increased loneliness among older adults, the rapid development of different digital e-services and applications have provided means for online socializing and, thus, decreased feelings of isolation and loneliness [ 17 ].…”
Section: Literature Landscapementioning
confidence: 99%
“…Recent reviews suggest that COVID-19 has created considerable anxiety, irritability, feelings of paranoia, and depression amongst community-dwelling older adults and people with serious comorbidities [ 10 ]. One Canadian study exploring loneliness amongst community-dwelling older adults found that 43.1% of older adults had experienced loneliness at least some of the time in the preceding week [ 11 ]. Factors associated with increased loneliness included having fair or poor health, changes to daily routine, and having a high concern for the pandemic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%